Endoscopic Stapedectomy: Collective Experience From a Large Australian Center. Issue 9 (October 2020) - Vaughan, Casey; Fox, Richard; Jufas, Nicholas; Kong, Jonathan H. K.; Patel, Nirmal P.; Saxby, Alexander J.
Abstract : Introduction: Endoscopic stapes surgery is a technically demanding procedure that is increasing in popularity. Surgical outcomes and complication rates have been demonstrated to be comparable to traditional microscopic techniques. The surgical outcomes for patients undergoing stapes surgery performed by the Sydney Endoscopic Ear Surgery Research Group are presented. Study Design: Retrospective review from prospectively gathered database. Setting: Tertiary referral centers. Patients: A retrospective case review of patients undergoing endoscopic stapes surgery performed by four surgeons between February 2015 and July 2019 was carried out. Sixty nine patients were identified, and assessed for demographics, functional results, and postoperative complications. Intervention: Endoscopic stapedotomy. Main Outcome Measure: Postoperative hearing results. Results: Sixty eight of 69 patients (98.6%) achieved an air-bone gap (ABG) closure of less than 20 dB. Sixty of 69 patients (87%) achieved and ABG closure of less than 10 dB. The average improvement of the ABG over four frequencies achieved was 26.5 dB (range, 0–61). Postoperative complications were infrequent and self-limiting. Six patients experienced dysgeusia without obvious chorda tympani injury, four patients developed short lived vertigo, and two patients experienced tinnitus. Conclusions: Endoscopically assisted stapes surgery represents a safe alternative to traditional microscopic techniques, with similar morbidity and audiological outcomes.